A Community-Based Study of Level and Determinants of Substance Use: Findings from Children Experiencing Homelessness in Major Cities of Northern Ethiopia - Asfaw Z; Mitiku M; Abebe HT; Atsbeha MT (Dove Medical Press, 2022)
Zinabu Asfaw,1 Mengistu Mitiku,2,3 Haftom Temesgen Abebe,2,4 Mussie Tesfay Atsbeha5 1Department of Public Health, Adigrat University, Adigrat City, Tigrai, Ethiopia; 2School of Public Health, Mekelle University, Mekelle City, Tigrai, Ethiopia; 3Research and Community Engagement Coordination Office, Mekelle University, Mekelle City, Tigrai, Ethiopia; 4Laboratory Interdisciplinary Statistical Data Analysis, Mekelle University, Mekelle city, Tigrai, Ethiopia; 5School of Medicine, Mekelle University, Mekelle City, Tigrai, EthiopiaCorrespondence: Zinabu Asfaw, Department of Public Health, Adigrat University, P.O. Box: 50, Adigrat City, Ethiopia, Email zinabu.asfaww@gmail.comBackground: Homelessness among children is a significant problem in most nations of the world. Children who experienced homelessness are most often unable to get secured and adequate housing. Such problems expose them to a range of destructive practices such as substance use. This study, therefore, was designed to evaluate the level and determinants of substance use by children who experienced homelessness in major cities of Northern Ethiopia.Methods: This cross-sectional study was undertaken from October 1, 2019 to February 30, 2020. We conducted street-based outreach searching to get a representative sample of the city's children who experienced homelessness and a total of 422 were recruited. The collected data were analyzed using SPSS version 20. Regression analysis was done to identify factors associated with substance use and statistical significance was declared at p < 0.05 and 95% confidence interval.Results: More than 80% of the children who experienced homelessness use alcohol, cigarette or chat. Marriage status of parents before the child experiences homelessness being divorce (AOR = 8.53, 95% CI: 1.87- 38.89), occupational status of mother being a daily laborer (AOR = 2.78, 95% CI: 0.83, 9.31), child relationship status with parents before child experiences homelessness (AOR = 0.08, 95% CI: 0.02- 0.30) and parents' residential status before child experiences homelessness being rural (AOR = 5.63, 95% CI: 1.77- 17.89) are the independent variables that established statistically significant association with the outcome variable, substance use.Conclusion and Recommendation: The majority of the children who experienced homelessness are exposed to substance use, particularly alcohol and cigarette. Efforts are needed by concerned bodies of the region to work on factors that predispose to homelessness and strategically safeguard the health and wellbeing of the children.Keywords: homelessness, substance use, children, Northern Ethiopia